COVID-19: Comprehensive Review of Transmission, Clinical Features, Diagnosis, Treatment, and Prevention Strategies - Alkharsan, Noor H (Technium BioChemMed, 2025)
The emergence of Coronavirus Disease 2019 (COVID-19) has been a considerable challenge to global health. This study surveys the origins, morphology, structure, and genome of coronaviruses, with a particular emphasis on SARS-CoV-2. The epidemiology of the virus is debated, emphasizing its transmission conventions, risk factors, and global case dispersal. Clinical manifestations range from mild symptoms to severe intricacies, such as critical respiratory distress syndrome and multi-organ dysfunction. The analysis outlines the mechanisms of viral entrance and duplication in cells of the host , highlighting the role of the ACE2 receptor. Screening strategies, such as polymerase chain reaction (PCR) and clinical evaluation, are studied. Current treatment options remain limited, with supportive care being the primary approach. Besides, preventive measures, including quarantine, personal protective equipment, and hygiene practices, are highlighted as key approaches to mitigate virus spread. The study contributes to the clarification of COVID19 by summarizing its characteristics, diagnostic strategies, treatment plans, and prevention procedures.